In‐tube Extraction and GC–MS Analysis of Volatile Components from Wild and Cultivated sea buckthorn (Hippophae rhamnoides L. ssp. Carpatica) Berry Varieties and Juice. Issue 4 (15th January 2013) - Socaci, Sonia A.; Socaciu, Carmen; Tofană, Maria; Raţi, Ioan V.; Pintea, Adela
ABSTRACT: Introduction: The health benefits of sea buckthorn ( Hippophae rhamnoides L.) are well documented due to its rich content in bioactive phytochemicals (pigments, phenolics and vitamins) as well as volatiles responsible for specific flavours and bacteriostatic action. The volatile compounds are good biomarkers of berry freshness, quality and authenticity. Objective: To develop a fast and efficient GC–MS method including a minimal sample preparation technique (in‐tube extraction, ITEX) for the discrimination of sea buckthorn varieties based on their chromatographic volatile fingerprint. Material and methods: Twelve sea buckthorn varieties (wild and cultivated) were collected from forestry departments and experimental fields, respectively. The extraction of volatile compounds was performed using the ITEX technique whereas separation and identification was performed using a GC–MS QP‐2010. Principal component analysis (PCA) was applied to discriminate the differences among sample composition. Results: Using GC–MS analysis, from the headspace of sea buckthorn samples, 46 volatile compounds were separated with 43 being identified. The most abundant derivatives were ethyl esters of 2‐methylbutanoic acid, 3‐methylbutanoic acid, hexanoic acid, octanoic acid and butanoic acid, as well as 3‐methylbutyl 3‐methylbutanoate, 3‐methylbutyl 2‐methylbutanoate and benzoic acid ethyl ester (over 80% of all volatile compounds). Principal component analysis showed that the first two components explain 79% of data variance, demonstrating a good discrimination between samples. Conclusion: A reliable, fast and eco‐friendly ITEX/GC–MS method was applied to fingerprint the volatile profile and to discriminate between wild and cultivated sea buckthorn berries originating from the Carpathians, with relevance to food science and technology. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : The health benefits of sea buckthorn ( Hippophae rhamnoides L. ) are well documented due to its rich content in bioactive phytochemicals as well as volatiles responsible for specific flavours and bacteriostatic action. The volatile compounds are good biomarkers of berry freshness, quality and authenticity. The objective of the study was to develop a fast and efficient GC–MS method including a minimal sample preparation technique (in‐tube extraction, ITEX) for the discrimination of sea buckthorn varieties based on their chromatographic volatile fingerprint. Twelve Romanian sea buckthorn varieties (cultivated or wild) where analyzed. Forty‐six volatile compounds were separated in the analyzed samples, with 43 being identified. The most abundant derivatives were ethyl esters of 2‐methylbutanoic acid, 3‐methylbutanoic acid, hexanoic acid, octanoic acid and butanoic acid, as well as 3‐methylbutyl 3‐methylbutanoate, 3‐methylbutyl 2‐methylbutanoate and benzoic acid ethyl ester (over 80% of all volatile compounds). Analyzing the samples volatile profile by principal component analysis (PCA) a good discrimination between sea buckthorn varieties was obtained (the first two components explained 79% of data variance), thus showing that ITEX/GC‐MS is a reliable and fast technique that can be used successfully for sample authenticity determination.